Implementation of Project Based Learning Event Management to Increase the Creativity of D3 Hospitality Students at Pertiwi University - Frisiska, Frisiska; Fahmi, Irsyad Nurul; Indrayanti, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Education is something that cannot be separated from human life. The thinking process will be greatly influenced by how individuals interact with the surrounding environment. In Indonesia, there are many formal educational institutions ranging from elementary schools to universities in the academic and vocational realms. The learning process will develop the cognitive, affective and psychomotor side of students to a better level. As a higher education institution, Pertiwi University applies the PBL (Project Based Learning) learning method in several courses in the D3 Hospitality study program. This research aims to find out how to apply the project-based learning method in the Event Management course at Pertiwi University. This research was carried out using qualitative methods which produced descriptive data. Project Based Learning in event management courses stimulates several domains of creativity such as Fluency, Originality, Flexibility, Elaboration, and Evaluation. Where these indicators play an important role in increasing student creativity in thinking and acting. Several indicators are embedded in various stages of this project, starting from the pre-event which encourages students to think and act with originality, fluency, elaboration and flexibility. At the Event (execution) stage, students are invited to think and act flexibly. And for post-event students are trained to improve elaboration and evaluation skills. In this way, students will be more creative in dealing with various symptoms that arise in the field. Apart from that, students also gain empirical experience in organizing and designing real events that are not just theoretical.